And God Said, "Let There Be Ritual. . . ." - Watkins, Nathan (International bulletin of mission research, 2020)
All human cultures are inclined toward ritualization. This article argues that Genesis 1-3 reveals God as the first cause of that inclination, establishing ritual behavior as a path for humans to safely and productively navigate the darkness and chaos of their fallen time and space. Missiologically, this implies that pre-Christian ritual should not be viewed as a danger to the contextualization process but valued as a window of insight into how that particular people group has been "groping their way toward God," and as an apparatus designed to help them "reach out and find him" (Acts 17:26-27).